Electrophysiological Measures of Visual Working Memory in Social Anxiety - Yuan, Jing; Mao, Ningning; Chen, Rongrong; Zhang, Qin; Cui, Lixia (Frontiers in Behavioral Neuroscience, 2020)
Abstract: Socially anxious individuals are very sensitive to threatening information in the environment, so visual working memory (VWM) is of great significance for them. However, the influence of social anxiety on VWM is unclear. In the present study, we aimed to investigate the VWM in individuals with social anxiety using electrophysiological techniques. Event-related potentials (ERPs) of high socially anxious (HSA) individuals and low socially anxious (LSA) individuals were recorded during a change-detection task with two memory conditions (two items and four items). Electrophysiological results indicated that compared with the LSA individuals, the HSA individuals had significantly more active contralateral delay activity (CDA) in condition of memorizing four items. However, there was no significant difference between the HSA group and LSA group in response accuracy in the conditions memorizing two and four items. From the electrophysiological results, individuals with high social anxiety could maintain more information in VWM. But maybe anxiety consume the available cognitive resources to compensate for the supposed to be impaired effective performance, so that individuals with high social anxiety perform as same as individuals with low social anxiety in terms of behavioral outcomes.